Exciton Dissociation and Charge‐Transport Enhancement in Organic Solar Cells with Quantum‐Dot/N‐doped CNT Hybrid Nanomaterials. (14th January 2013) - Lee, Ju Min; Kwon, Byoung‐Hwa; Park, Hyung Il; Kim, Hoyeon; Kim, Min Gyu; Park, Ji Sun; Kim, E Su; Yoo, Seunghyup; Jeon, Duk Young; Kim, Sang Ouk
<x xml:space="preserve">Abstract</x> The incorporation of InP quantum‐dot/N‐doped multiwalled carbon nanotube (QD:NCNT) nanohybrids in the active layer of poly(3‐hexylthiophene)/indene−C60 bisadduct (P3HT/ICBA) bulk‐heterojuction solar cells enhances VOC and JSC. The QDs encourage exciton dissociation by promoting electron transfer, while the NCNTs enhance the transport of the separated electrons and eventual charge collection. Such a synergistic effect successfully improves the power conversion efficiency (PCE) from 4.68% (reference cells) to 6.11%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>